A Miniature and Low-Power-Consumption Stress Measurement System for Embedded Explosive in Multilayer Target Penetration - Yu Hang; Fei Shang; Shang Gao; Deren Kong; Xuehui Zhang (Shock and Vibration)
When a penetrator penetrates a target, security issues such as detonation and deflagration sometimes occur in the embedded explosive under an extreme environment with high overload and severe mechanical shock. Explosives withstand multiple impact stresses with high amplitudes during a multilayer target penetration (MTP) process. Manganin pressure gauges and external dynamic testing systems are common instruments to evaluate explosive safety. However, this method is unsuitable for an MTP experiment where the penetrator flies with a long distance. This article proposes a stress measurement system (SMS) installed in a penetrator for explosive stress detection based on a qualitative analysis for the stress characteristics of the explosive. A high-strength mechanical structure is designed for the SMS to survive in the MTP environment. A low-power management mechanism realized by dual MCUs (STM32 + FPGA) is proposed to reduce the power consumption of the SMS. An experimental investigation is carried out to verify the feasibility of the measurement system designed in this paper. An MTP numerical simulation is carried out to reveal the characteristics of stress occurring and propagating in the explosive. An MTP experiment is conducted and the impact stresses on the explosive surface are measured by the fabricated SMS prototypes. The measurement results are consistent with the simulation results, which indicate that the prototypes have the abilities of high-precision data acquisition and storage in the MTP experiment.